Strategi Guru PPKn dalam Penguatan Nilai Karakter Disiplin Belajar Perserta Didik melalui Pembelajaran Pendidikan Pancasila dan Kewarganegaraan di SMP Negeri 9 Kota Pariaman - Farhan, Farhan; Jaenam, Jaenam; Rudagi, Reindy (Lembaga Yasin AlSys, 2023)
This study aims to describe the PPKn teacher's strategy design in strengthening the character values of student learning discipline through learning Education and citizenship at SMP Negeri 9 Pariaman, to describe the implementation of Civics Teacher strategies in Strengthening Discipline Character Values for Student Learning through Pancasila and Citizenship Education Learning in Middle School Negeri 9 Kota Pariaman and to reveal the obstacles experienced by Civics teachers in Strengthening the disciplinary character values of students at SMP Negeri 9 Pariaman. The type of research used in this study was qualitative research using descriptive research methods with informant subjects being school principals, curriculum representatives, Civic Education teachers and VIII/4 grade students at SMP Negeri 9 Pariaman. The data collection used included observation, interviews and documentation.The results of this study indicate that the strategy of PPKn Teachers in Strengthening Discipline Character Values of Student Learning through Pancasila and Citizenship Education Learning at SMP Negeri 9 Kota Pariaman has been applied to students, namely coming to school on time, always providing motivation before learning begins, starting and ending learning with time implementing Civics teacher strategies in strengthening disciplinary character values that have also been applied to students are teachers using habituation strategies, teachers as examples or models, teachers give rewards and teachers give punishment, these four strategies have been implemented by teachers PPKn at SMP 9 Negeri 9 Pariaman the obstacle faced by PPKn teachers in strengthening disciplinary character values is the lack of interest or awareness of students to learn and the environment in which students play, these two obstacles are the inhibiting factors for PPKn teachers in implementing strengthening the character values of school discipline learning.